Results of the dental treatment in children with bruxism - Kirenia Pieri Silva; Clotilde de la Caridad Mora Pérez; Ivelise Álvarez Rosa; Boris Abel González Arocha; Beatriz García Alpízar; Lilliam Morales Rosell (Medisur)
Background: bruxism is a habit associated to stress and to occlusal disturbances which can be solved applying an odontological treatment. Objective: to evaluate the effectiveness of the odotological treatment in students from 5 to 11 years with bruxism. Methods: a study of cuasiexperimental intervention design of type before and after in all the children with bruxim (52), with ages of 5 to 11 elderly years, belonging to Health Area II. Cienfuegos. An oral exam to each child was made; parents and teachers were interviewed as well. Studied variables were: Age, sex, the bruxism's grade of affectation, psychological diagnosis and symptoms and the bruxism's signs. The results present itself in draw of numbers and percentages. Results: the bigger affectation predominated in the female sex from 6 to 11 elderly years and the psychological diagnosis of severe disorders. When examining the signs and symptoms of bruxism before the intervention, the more frequent were the dental squeaking and the dental squeezing. After applying the treatment, more than the half of the children improved his symptomatology in relation to the initial status, and an improvement of over the 70 % in the event of the muscular pain was achieved. Conclusion: the effectiveness of the dental treatment in the improvement of the signs and symptoms of the bruxism was demonstrated.